Evaluating the Predominant Attitudes of Teachers and Principals Towards Educational Programs for Gifted Students in Elementary Schools - Hamdi, Yahya Ali (Journal of Educational and Psychological Sciences, 2021)
The current systematic review of the literature (SLR) is divided into different sections starting with the introduction section. That being said, there is a discussion section that broadly evaluates different topics in addition to the summary findings that emerge from the study by discussion, there are mixed results about teachers’ prevailing attitudes toward gifted students, and there are programs developed in order to promote the special needs of gifted children that teachers and school administrators are aware of. The study methodology depends on conducting tests and examining opinions about the subject and the guidance that it applied, and concluded that the gifted show distinctive qualities that differ from other students, and therefore they need special intervention programs to achieve the best educational results, and there are some school principals and talented people who support the programs that It aims to help the gifted, and there are others who do not support these programs, and various governments support programs that help Gifted students in the educational process and dealing with them in a way that supports their talents, and there are recommendations that were deduced from the study, which is that attention should be paid to identifying gifted students in educational institutions to work on their involvement in educational programs for the gifted, especially in primary schools, and there must be a positive response towards gifted education programs by Teachers and school administrators, work to develop these programs.